2009
DOI: 10.1111/j.1461-9563.2009.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of imidacloprid on the abundance of surface‐ and soil‐active nontarget fauna in turf

Abstract: 1 Outbreaks of root-feeding scarab larvae in turfgrass are widely managed through preventive applications of imidacloprid. Long-residual activity and application before feasible scouting probably lead to its overuse and overexposure. 2 Recent investigations revealed a selective impact of imidacloprid (not trichlorfon or halofenozide) on certain nontarget turf arthropods, motivating the present study on the persistence of abundance effects over 6 years of annual applications. 3 Arthropods were sampled monthly (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 46 publications
4
35
0
Order By: Relevance
“…A germinated seed bioassay found that clothianidin seed treatments adversely affected 16 carabid species. Six years of annual imidacloprid soil‐applications in turf reduced adult staphylinid and carabid captures . Our results agree with the findings of these studies and also provide evidence of even higher reductions (20.2 and 34.5%) in predator abundance than the levels (∼16%) reported in the meta‐analysis study…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A germinated seed bioassay found that clothianidin seed treatments adversely affected 16 carabid species. Six years of annual imidacloprid soil‐applications in turf reduced adult staphylinid and carabid captures . Our results agree with the findings of these studies and also provide evidence of even higher reductions (20.2 and 34.5%) in predator abundance than the levels (∼16%) reported in the meta‐analysis study…”
Section: Discussionsupporting
confidence: 91%
“…Pooled together as a feeding guild, predators (primarily minute pirate bugs, ladybird beetles, lacewings, spiders, ground beetles, and rove beetles) in the epigeal and foliage communities were significantly less abundant in the insecticide treated plots by 20.2 and 34.5%, respectively. Other studies have reported similar negative effects on insect predators after exposure to neonicotinoid residues . The predator composition and abundance in imidacloprid seed treated and untreated corn fields over a 5‐year period showed adverse effects on Heteroptera, Staphylinidae, and to a lesser extent, Carabidae .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Preventative control measures rely on the application of insecticides, often neonicotinoids, around the time of egg hatch but before white grubs are detected . Neonicotinoid insecticides applied for preventative control of white grubs have consequences for insect pollinators and beneficials, and soil‐dwelling invertebrates . These non‐target impacts of grub control create opportunities for alternatives such as increasing plant tolerance to damage.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, chemical control of the GPA population has little efficiency in the peach orchard management (Cravedi and Cervato 1997). In addition, the use of effective systemic insecticides such as imidacloprid has raised concerns in an increasing number of countries because of their possible non-targeted impact on beneficial insects (Decourtye et al 2004;Peck 2009). Natural enemies as biological control means or novel approaches such as kaolin treatments have been alternatively proposed (Barker et al 2007;Gentz et al 2010).…”
Section: Introductionmentioning
confidence: 99%